Korelasi Tingkat Pengetahuan Feeding Rules Ibu dengan Status Gizi Batita - Meivita Dewi Purnamasari; Gita Sabrina Pratiwi; Aprilia Kartikasari (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: Knowledge can influence behaviour. Feeding is a factor that affect nutritional status of children. This study aims to describe the relationship between the level of mother’s knowledge about feeding rules and the nutritional status of toddlres.Methods: This study used a cross-sectional method. This research was conducted at the posyandu in Bancarkembar area with a total sampling technique. The number of samples is 68 respondents who meet the inclusive criteria. The research was conducted by giving a questionnaire the level of mother’s knowledge about feeding rules and antropometric measurements (weight and length) on toddlers to determine the nutritional status of toddlers. The two variables were tested for correlation using Sommers’d.Results: The results showed that there was a relationship between the level of mother’s knowledge about feeding rules and the nutritional status of toddlers with p-0,042 (p<0,05).Conclusion: The level of mother’s knowledge about feeding rules is related to the nutritional status of toodlers. This research recommends feeding rules education to mothers.